2009
DOI: 10.1111/j.1742-7843.2008.00366.x
|View full text |Cite
|
Sign up to set email alerts
|

Antigenotoxic, Antioxidant and Lymphocyte Induction Effects Produced by Pteropodine

Abstract: Pteropodine is a heterohimbine-type oxindole alkaloid specifically isolated from 'Cat's claw' ( Uncaria tomentosa ), a plant that has shown cytostatic, anti-inflammatory and antimutagenic properties and is used in traditional medicine to cure a number of diseases. In this report, we studied the ability of pteropodine to decrease the rate of sister-chromatid exchanges and micronucleated polychromatic erythrocytes in mice administered doxorubicin. We also determined its capacity to induce lymphocyte production i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 33 publications
0
22
0
4
Order By: Relevance
“…It has been reported that daunorubicin induces severe chromosome damage by measuring sister chromatid exchanges (SCE) and micronuclei (MN). For this reason, it is used as a positive control in experimental studies (Bommu et al, 2008: Paniagua-Pérez et al, 2009. In contrast, HLEE produced neither genotoxic nor cytotoxic damage in the present study.…”
Section: Discussionmentioning
confidence: 75%
“…It has been reported that daunorubicin induces severe chromosome damage by measuring sister chromatid exchanges (SCE) and micronuclei (MN). For this reason, it is used as a positive control in experimental studies (Bommu et al, 2008: Paniagua-Pérez et al, 2009. In contrast, HLEE produced neither genotoxic nor cytotoxic damage in the present study.…”
Section: Discussionmentioning
confidence: 75%
“…Among the most abundant alkaloids found in this plant, there is a mixture of pentacyclic oxindole stereoisomers that differ in configuration at chiral centres in the positions 3, 7, 15, 19 and 20 (Figure 2A). In attempting to explain the anti-neoplastic effects of U. tomentosa , researchers have demonstrated interest in this group of substances, based on previous observations that gave them credit for its anti-inflammatory activity [8], [9]. However, it is important not to overlook the fact that cancer is a vast group of diseases that may vary substantially among them.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, reference to the use of alkaloids isolated from U. tomentosa goes as far back as to 1985, when Wagner and colleagues [8] observed that four out of six oxindole alkaloids present in this plant caused a pronounced enhancement of phagocytosis, both in vitro and in vivo . More recently, studies with several of these isolated alkaloids yielded reports on their antioxidant, immunomodulant [9] and even anti-neoplastic properties [10], [11]. Other studies, however, have demonstrated that compounds different than the oxindole alkaloids may be at least partially responsible for the observed effects.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies have clearly shown the potential of the antioxidant Ut , and its potent radical scavenger activity was confirmed by several assays including the following: the capacity to reduce the free radical diphenylpycrilhydrazyl (DPPH assay) [30, 31], the reaction with the superoxide anion, peroxyl [30], and hydroxyl radicals [30] as well as with the oxidant species, hydrogen peroxide, and hypochlorous acid [30, 32], and the TEAC assay [10]. The antioxidant activity of Ut extracts was further assayed through determination of TBARS production (using rat liver homogenates and sarcoplasmic reticulum membranes) and by the inhibition of free radical-mediated DNA-sugar damage [30, 33].…”
Section: Discussionmentioning
confidence: 98%
“…The antioxidant activity of Ut extracts was further assayed through determination of TBARS production (using rat liver homogenates and sarcoplasmic reticulum membranes) and by the inhibition of free radical-mediated DNA-sugar damage [30, 33]. These assays were primarily in vitro tests with one in vivo test [31]. Despite this strong evidence, no differences in oxidative stress were found between groups that received or did not receive Ut , as assessed by lipid peroxidation (TBARS) and protein carbonyls.…”
Section: Discussionmentioning
confidence: 99%